LEGAL PROTECTION OF PARTICIPANTS IN THE PROCUREMENT OF TECHNICAL EQUIPMENT AGAINST MISUSE OF EQUIPMENT DESIGN - Malau, Parningotan; Handayani, Pristika; Ringo, Desron Siringo (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The submission of a procurement request for engineering equipment is, of course, accompanied by a budget plan for the manufacture of the equipment. In practice, many companies that conduct engineering equipment procurement auctions often obtain engineering equipment designs from one tender participant to be used by other tender participants without disclosure. This causes injustice to tender participants whose engineering equipment designs are used without their knowledge or consent. The absence of registration of industrial designs results in no protection of industrial design rights, which can lead to imitation or plagiarism of the design, and there is even the possibility of using the design in the future. Another problem that also arises is that the engineering equipment designed or created is not mass-produced, as it is only produced for specific conditions. The formulation of the problem in this study concerns how to regulate engineering equipment design, how to protect engineering equipment procurement participants from misuse of engineering equipment design, and what solutions are available for addressing misuse of equipment design. The research methodology used was normative research. In Indonesia, industrial design, also known as industrial product design, has been recognized as a distinct entity from copyright. In 2000, a law specifically regulating industrial design was enacted, known as the Industrial Design Law. Additionally, the regulation regarding the layout of integrated circuits is outlined in Law Number 32 of 2000 concerning Integrated Circuit Layout Design. The protection of engineering tool designs can only be carried out through repressive efforts, both criminally and civilly. This protection is only based on whether the engineering tool procurement participant has an industrial design certificate. So that the engineering tool procurement participant firmly owns the legality of the design, solutions that can be taken include: First, the need for preventive legal regulations in the form of obligations from the engineering tool procurement company with the engineering tool procurement participant in the form of a written agreement containing an agreement to maintain the confidentiality of information. Second, there is a need for ease in obtaining industrial design certificates by the Directorate General of Intellectual Property Rights. Third, there is a need for supervision and socialization of all business entities participating in the procurement of engineering tools to prevent the misuse of engineering tool designs.